If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+4(x+4)=60
We move all terms to the left:
7x+4(x+4)-(60)=0
We multiply parentheses
7x+4x+16-60=0
We add all the numbers together, and all the variables
11x-44=0
We move all terms containing x to the left, all other terms to the right
11x=44
x=44/11
x=4
| 5x(3x-1)=100 | | 3x2+10x–18=0 | | 3x+0,2=17-x | | 52525-75m+175m=56375-175m | | 5(3w+7)/3=-3 | | 9n-6=6+6n | | 8(4s+6)=176 | | C^+6c+8=0 | | 9(u+3)=36 | | 3(q-3)=24 | | -a-7=-8a | | y2-7y+4=0 | | 2(g+5)=3(2g-1) | | 5x-(2x-5)=x+1 | | 6f+3=4f-11 | | (2k+1)/(3+k)=-1 | | 92+x-152=175 | | 5(x+16)+7x=128 | | 5x+2+2x=12-3 | | 2k+1=-1 | | 3=8r+23 | | 5t+1=14 | | -3+x/3=3 | | 40+6m=5 | | 3x*x-5x-40=0 | | 6p+18=9p-3 | | 9^(3n)=27^(n+2) | | 42=6(y+10) | | v=2*2.5/0.3E+1 | | (2x+4)/2=120 | | 6x+114=16x-6 | | 2(-4-3x)-3x=2(2x+3)-2 |